Penyuluhan Peningkatan Pengetahuan Wanita Usia Subur Tentang Pencegahan Anemia Melalui Edukasi Gizi Seimbang di PMB Imelda Tae Sekadau Tahun 2026 - Hearty Efifania Ose Payon; Silvia Finida Hannisa; Asri Fitri Yati (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2026)
Anemia remains a significant public health problem commonly experienced by women of reproductive age (WRA) due to inadequate iron intake, blood loss during menstruation, and limited knowledge of healthy dietary patterns and balanced nutrition. This condition may lead to decreased productivity, reduced immune function, and an increased risk of complications in future pregnancies. This community service activity aimed to improve the knowledge of women of reproductive age regarding anemia prevention through balanced nutrition education at PMB Imelda Tae Sekadau in 2026. The method used in this activity was health education through lectures, discussions, and question-and-answer sessions. The activity was conducted through several stages, including opening, material delivery, evaluation, and closing sessions. A total of 11 women of reproductive age participated actively in the counseling session. The evaluation results indicated that more than 85% of participants were able to answer the questions provided after the material presentation, suggesting an improvement in understanding of anemia, its signs and symptoms, impacts, and the importance of implementing balanced nutrition in daily life as an effort to prevent anemia. Therefore, this counseling activity was considered effective in enhancing the knowledge of women of reproductive age regarding anemia prevention through balanced nutrition education.